2010
DOI: 10.1002/eco.105
|View full text |Cite
|
Sign up to set email alerts
|

Modelling rainfall interception loss in forest restoration trials in Panama

Abstract: A modified Liu analytical model of rainfall interception (I c ) by tree canopies was evaluated using rainfall, throughfall and stemflow data collected from forest restoration trials in the Republic of Panama. The model uses an introduced approach to estimating the water storage capacities of tree boles, which has a more realistic physical basis than earlier iterations of the Liu model. Study species (Acacia mangium, Gliricidia sepium, Guazuma ulmifolia, Ochroma pyramidale, and Pachira quinata) were selected on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 68 publications
0
15
0
Order By: Relevance
“…Clear impacts of vegetation structure on rainfall partitioning like those described by Hodnett et al ., , Crockford and Richardson, , Huber and Iroumé, , Fleischbein et al ., , Brauman et al ., , Carlyle‐Moses et al ., and Mair and Fares, were not found in this study. Species diversity and LAI values for different land‐use types did not explain differences in throughfall, but this may because different species influence throughfall in different ways (Park and Cameron, ).…”
Section: Discussionmentioning
confidence: 99%
“…Clear impacts of vegetation structure on rainfall partitioning like those described by Hodnett et al ., , Crockford and Richardson, , Huber and Iroumé, , Fleischbein et al ., , Brauman et al ., , Carlyle‐Moses et al ., and Mair and Fares, were not found in this study. Species diversity and LAI values for different land‐use types did not explain differences in throughfall, but this may because different species influence throughfall in different ways (Park and Cameron, ).…”
Section: Discussionmentioning
confidence: 99%
“…Carlyle‐Moses et al . () developed an improvement to S t estimates for individual trees using a metric called the stemflow funnelling ratio (Herwitz, ). The funnelling ratio ( F ) is basically an areal comparison of P with stemflow generated by the outlying crown portions: F=PnormalsB×Pwhere P s is the stemflow volume and B is the trunk basal area (Herwitz, ).…”
Section: Methods For Estimating Interception Water Storagementioning
confidence: 99%
“…The Liu model is much less demanding than other interception models such as that of Rutter et al (1971) and Gash (1979) in terms of data requirements; yet it has been found to produce results of comparable accuracy to these models (Liu, 2001;Carlyle-Moses and Price, 2007). The Liu model also incorporates exponential wetting of the canopy, which more accurately reflects the actual process of canopy wetting than alternatives such as the Gash (1979) model which requires that canopy storage capacity be satisfied before drainage occurs (Carlyle-Moses et al, 2010). The reformulated model is:…”
Section: Modeling and Parameter Derivationmentioning
confidence: 98%
“…The Liu model has also not been as widely used as other interception models (Muzylo et al, 2009), and this study will evaluate its performance in estimating interception for forest types other than those in which it has already been applied (e.g. Liu, 2001;Carlyle-Moses and Price, 2007;Carlyle-Moses et al, 2010). Should it prove to be satisfactory, the Liu model could then be used to predict how reforestation and the transition to a mixed hardwood forest will affect water partitioning in forest stands of differing type and age in the GF.…”
Section: Introductionmentioning
confidence: 96%